cGAS-STING pathway as a promising target for digestive diseases: insights from natural plant products - Long, Dan; Mao, Chenhan; Zhu, Ying; Xu, Yin (Frontiers in Nutrition, 2025)
Digestive diseases remain a major challenge to public health systems globally. Cyclic GMP-AMP synthase (cGAS) and stimulator of interferon gene (STING) play important roles in innate immunity as well as inflammatory responses. Dysregulation of the cGAS-STING pathway has been demonstrated to be an important pathogenetic mechanism in diverse gastrointestinal diseases. Therefore, targeting the cGAS-STING pathway is a potential therapeutic strategy for digestive diseases. Encouragingly, increasing studies have revealed that natural plant products are promising candidates for the treatment of digestive disorders. This review discussed the research progress of cGAS-STING pathway mediating common digestive diseases, including inflammatory bowel disease, liver disease, colorectal cancer, gastric cancer, esophageal cancer, pancreatitis, and pancreatic cancer. In addition, we systematically summarized recent advances in the treatment of gastrointestinal disorders with phytochemicals that target the cGAS-STING pathway.